Power-flex stretching get maximum flexibility in minimum time : super flexibility and strength for peak performance - De Angelis, David (Meyer & Meyer Sport, 2010)
Do you need to achieve a higher level of flexibility? Does your sports discipline require the strength out of common run? You can really express all your athletic capabilities only developing your strength and flexibility qualities at maximum. This book reveals the secrets of developing excellent strength and flexibility qualities.